2010
DOI: 10.1002/app.33003
|View full text |Cite
|
Sign up to set email alerts
|

Removal of arsenic from aqueous solutions by an adsorption process with titania–silica binary oxide nanoparticle loaded polyacrylonitrile polymer

Abstract: In this study, we fabricated a new hybrid adsorbent, titania-silica binary oxide (TiO 2 -SiO 2 )-polyacrylonitrile (PAN), by loading nanosized sol-gel-derived TiO 2 -SiO 2 onto a porous PAN polymer for enhanced arsenite [As(III)] and arsenate [As(V)] species removal from aqueous media. The resulting sorbent was characterized by thermogravimetric analysis, scanning electron microscopy, X-ray powder diffraction, IR spectroscopy, and porosity measurements. The sorption process for the removal of As(V) and As(III)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The BET surface area of TiO 2 , SiO 2 , and TiO 2 .SiO 2 NPs is found to be in the range of 60.081 to 75.017 m 2 /g. This sizeable increase in surface area of TiO 2 .SiO 2 NPs may be due to the SiO 2 limiting the agglomeration of TiO 2 particles . The samples exhibited mesoporosity and macroporosity with the pore volume ranging from 0.1019 to 0.4204 cm 3 /g.…”
Section: Resultsmentioning
confidence: 99%
“…The BET surface area of TiO 2 , SiO 2 , and TiO 2 .SiO 2 NPs is found to be in the range of 60.081 to 75.017 m 2 /g. This sizeable increase in surface area of TiO 2 .SiO 2 NPs may be due to the SiO 2 limiting the agglomeration of TiO 2 particles . The samples exhibited mesoporosity and macroporosity with the pore volume ranging from 0.1019 to 0.4204 cm 3 /g.…”
Section: Resultsmentioning
confidence: 99%
“…A shift between optimum As(V) removal pH and pH PZC of NH 4 -NZ-Y is observed that it may be related with ammonia dissolved during adsorption. Based on pre-viously reported results, 61 as pH is lower than 6.8, the amount of multivalent species were dominated by H 3 AsO 4 and H 2 AsO 4 − in which the surfaces of adsorbent are positively charged and could bind negatively charged H 2 A-sO 4 − anions, which was responsible for the adsorption via electrostatic attraction and/or ligand change mechanism. 62 For influence of pH value in the solution, in the pH range of 1.5-5.0 63 electrostatic attraction occurs since As(V) generally exists in the forms of H 2 AsO 4 − and HAsO 4 2− and the adsorbents possess negative charge, facilitating arsenic removal.…”
Section: 1 Influence Of Phmentioning
confidence: 95%
“…Therefore, As (III) has been oxidized to As (V) and then removed from water by various technologies such as oxi-dation, reverse osmosis, chemical coagulation followed by filtration and adsorption. [3][4][5] Among removal technologies, adsorption is the most promising technology due to the advantages of treatment stability, easy operation, lower environmental impacts, and low cost if suitable adsorbent can be either chosen or designed. Recently many materials have been used and studied as adsorbent for removal of As (III) and As (V) from water.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles are added to water as powder or are incorporated in conventional remediation methods to increase their efficiency, e.g. in membranes or polymers (Nilchi et al 2011;Theron et al 2008 (Fan et al 2003). Commercial polyaluminum coagulant forms large Al nanoclusters when produced with high total Al concentrations at high temperatures for a long time (Chen et al 2006 ) are the largest aqueous aluminum hydroxide complexes with 1 nm diameter and 1-2 nm length.…”
Section: Introductionmentioning
confidence: 99%